Reduction in Cutis Verticis Gyrata after Transsphenoidal Pituitary Resection of Growth Hormone–Secreting Adenoma - Daniel Pinggera; Delia Anna Marsoner; Marcel Seiz-Rosenhagen; Claudius Thomé; Christian Franz Freyschlag (Indian Journal of Neurosurgery)
Abstract